THE SIGNIFICANCE AND THEORETICAL BASIS OF DISTANCE LEARNING OF GEOGRAPHY IN HIGHER EDUCATION - S. E. Baymuradova (Journals Park Publishing, 2023)
Information is given about the importance of remote teaching of geography in the higher education system, theoretical foundations, level of study, problems, effectiveness of teaching, and defined tasks.
Keywords: Distance education, distance education, geography teaching methodology, flipped classroom, blended learning, ICT, EATR, etc.